Investigation on Efficient FPGA Architectures for Image Coding Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In this research, we provide an effective hardware architecture for various image processing, enhancement, and filtering algorithms that is based on FPGAs. The inherent spatial and temporal parallelism in FPGA architecture makes them a popular choice as implementation platforms for real-time image processing applications. The filters are applied by iteratively cycling over an image's pixels using a windowing operator method. Software becomes less effective and real-time hardware solutions are required as picture sizes and bit depths increase. While the findings shown here are for a picture with a resolution of 585 x 450 pixels, the stated method may be used to photos of any resolution, provided that the FPGA memory can accommodate it. The design was developed using the Nexys3 board and Xilinx Spartan-6 FPGA in mind.